Memo from George Barsky to Max Bredig - Barsky, George (1940)
Memo in which George Barksy tells Max Bredig (1902-1977) that "Landis" cannot help Fritz Hochwald (1897-1968). Barksy reports that Franz Friedrich Nord (1889-1973) suggested sending the papers which were seemingly attached to the memo.
Keywords: Bredig, Max Albert, 1902-1977; Barsky, Georg; Hochwald, Fritz G., 1897-1968; Nord, Friedrich Franz, 1889 -1973; Emigration and immigration